Quantifying the Impact of Canopy Structural Characteristics on Soil Temperature Variations in Different Bamboo Communities - Tingting Ma; Xinge Nan; Renwu Wu; Hai Yan; Na Wu; Juan She; Zhiyi Bao (Atmosphere, 2023)
Soil temperature plays an important role in soil respiration, which is related to the atmospheric carbon cycle. In addition to its own physical and chemical properties, soil temperature is also influenced by external environmental factors, including plants. Therefore, it is relevant to explore the relationship between plant characteristics and soil temperature. This study was conducted in Hangzhou, China. The influence of canopy structural characteristics of bamboo communities on soil temperature was investigated in detail by means of field measurements. In summer, the canopy structure of bamboo communities reduced the soil temperature by up to 3.0–3.8 °C, 2.4–3.4 °C, and 2.3–3.0 °C at 5 cm, 10 cm, and 20 cm, respectively. In winter, the canopy structure of bamboo communities increased soil temperature by up to 0.1–0.4 °C, 0.1–0.6 °C, and 0.2–0.7 °C at 5 cm, 10 cm, and 20 cm, respectively. The leaf area index and canopy cover significantly affected the soil temperature, while the effect of the sky view factor was minimal compared to other factors. We also discovered that soil temperatures at different depths interact and are influenced by the air temperature. These findings provide a more reasonable bamboo canopy plan to improve the urban environment effectively.